Higher education in 21st century: An analysis of ICT integration for teaching and learning in Pakistan - Nisar Ahmad; Arif Alam; Ikram Shah (Knowledge Management & E-Learning: An International Journal)
Information Communication Technology (ICT) is ubiquitous in the 21st century, hence both educators and learners need to integrate relevant ICT resources in their teaching and learning practices, to meet stakeholder’s expectations and keep abreast with the race of technological advancement. The current research focuses on the analysis of ICT integration elements i-e availability, accessibility, usability and usefulness for teaching and learning in higher education institutions (HEIs) in the Hazara region of Khyber Pakhtunkhwa, Pakistan, characterized as an underdeveloped and mountainous region with limited access to ICT tools in the education system. A mixed method approach was used in this study, with the latest version of SPSS software (version 27) to analyze the data. The findings of the study indicate that there is no significant difference between the respondents in ICT integration for learning as Mann-Whitney U = 6079 and p < 0.001 in higher education institutions (HEIs). However, a significant difference was observed between the respondents for teaching as Mann-Whitney U = 9463 and p > 0.374. Subsequent findings revealed more significant p-values and higher means for learning than teaching. This indicates that the use of ICT tools has a positive and significant impact on learning.